A novel inhibitor of the PI3K/Akt pathway based on the structure of inositol 1,3,4,5,6-pentakisphosphate - Falasca, M; Chiozzotto, D; Godage, H; Mazzoletti, M; Riley, A; Previdi, S; Potter, B; Broggini, M; Maffucci, T (Nature Publishing Group, 2010)
Background: Owing to its role in cancer, the phosphoinositide 3-kinase (PI3K)/Akt pathway is an attractive target for therapeutic intervention. We previously reported that the inhibition of Akt by inositol 1,3,4,5,6- pentakisphosphate (InsP5) results in anti-tumour properties. To further develop this compound we modified its structure to obtain more potent inhibitors of the PI3K/Akt pathway.Methods: Cell proliferation/survival was determined by cell counting, sulphorhodamine or acridine orange/ethidium bromide assay; Akt activation was determined by western blot analysis. In vivo effect of compounds was tested on PC3 xenografts, whereas in vitro activity on kinases was determined by SelectScreen Kinase Profiling Service.Results: The derivative 2-O-benzyl-myo-inositol 1,3,4,5,6-pentakisphosphate (2-O-Bn-InsP5) is active towards cancer types resistant to InsP5 in vitro and in vivo. 2-O-Bn-InsP5 possesses higher pro-apoptotic activity than InsP 5 in sensitive cells and enhances the effect of anti-cancer compounds. 2-O-Bn-InsP5 specifically inhibits 3-phosphoinositide- dependent protein kinase 1 (PDK1) in vitro (IC 50 in the low nanomolar range) and the PDK1-dependent phosphorylation of Akt in cell lines and excised tumours. It is interesting to note that 2-O-Bn-InsP5 also inhibits the mammalian target of rapamycin (mTOR) in vitro.Conclusions: InsP5 and 2-O-Bn-InsP5 may represent lead compounds to develop novel inhibitors of the PI3K/Akt pathway (including potential dual PDK1/mTOR inhibitors) and novel potential anti-cancer drugs.